Tradition, Family Issues, and Educational Values in a Chinese-Canadian Living in Toronto: Analysis on Turning Red (2022) - Ramadhani, Jihan Medina; Wardoyo, Cipto (Program Studi Pendidikan Bahasa Inggris, 2025)
This research examines the animated film Turning Red as a narrative that explores cultural identity, generational conflict, and self-discovery within the Chinese-Canadian diaspora. By employing qualitative research and narrative text analysis, the research focuses on how the film portrays the tension between traditional values and modern influences in shaping the protagonist Mei Lee’s identity. The story follows Mei, a 13-year-old Toronto teenager, as she navigates adolescence, family expectations, and her transformation into a red panda, which symbolizes emotional change. The film highlights the clash between Mei and her mother Ming, who adheres strictly to cultural traditions, emphasizing Mei’s desire to forge her own path. Through empathy and communication, Mei and Ming reconcile their differences, highlighting the importance of familial relationships. The red panda serves as a powerful symbol for self-acceptance and the blending of heritage with personal growth. Overall, Turning Red offers valuable insights into cultural representation, identity formation, and the universal theme of family.